LA NADA COMO CATEGORÍA ONTOLÓGICA EN EL VIDEOJUEGO: ANÁLISIS DE SAD SATAN - Dr. Aarón RODRÍGUEZ SERRANO, (Fonseca, Journal of Communication, 2023)
This study tries to explore the idea of nothingness as an ontological category on the construction of virtual worlds. The research is framed in the metaphysical study of video games, trying to go over the narratological readings, and asking about the way in which the designing of virtual worlds is, at the same time, indebted to and divergent from our concrete experience of the real world.